Thermoelectric Property of Ag‐doped ZnSb/Few‐Layer‐Graphene Composites. (27th April 2016) - Choi, Kwang Min; Lee, Eunsil; Ko, Jieun; Kim, Jong‐Young; Lee, Soonil; Seo, Won‐Seon; Choi, Soon‐Mok; Lee, Kyu Hyoung; Kim, Seung Joo
Abstract : Abstract : We have successfully synthesized the composites of Ag‐doped zinc antimonide (Ag‐ZnSb) and few‐layer‐graphene (FLG) by high‐energy‐mechanical milling and spark plasma sintering using Ag‐ZnSb ingot and FLG as raw materials. The FLG/Ag‐ZnSb shows 22%‐reduced lattice thermal conductivity by increased phonon boundary scattering due to embedded FLG. The electrical conductivity of the composites was decreased due to reduced carrier concentration, while the Seebeck coefficient of the composites was increased by electron donating effect of FLG. The maximum figure of merit, ZT, of 0.86 was observed at 630 K. The peak ZT temperature in the FLG/Ag‐ZnSb cases ( 630 K) were higher than the pristine Ag‐ZnSb compound ( 580 K) resulting in advantages for the higher temperature power generation.